Pengaruh Bermain Konstruktif dengan Media Clay Terhadap Kemampuan Motorik Halus Anak Usia 5-6 Tahun di Desa Maria Utara Kecamatan Wawo Kabupaten Bima - Ummi Kalsum; I Made Suwasa Astawa; Ika Rachmayani; Baik Nilawati Astini (Indonesian Journal of Elementary and Childhood Education, 2021)
This research was setting by the lack of fine motor skills of children. This was because the children’s fine motor development when playing is still not effective, in this research use the constructive play method using clay media to improve children’s fine motor skills. Therefore, this research aims to determine the effect of constructive play with clay media to the fine motor skills of children aged 5-6 years in North Maria Village, Wawo District, Bima Regency in 2020. This research was conducted during of Covid-19 pandemic while still paying attention to health protocol. The population and sample consisted of 8 children who were divided into 4 children in the control group and 4 children in the experimental group. Based on the normality and homogeneous assumption testing, the normality test on the difference between the pretest and posttest with a significance level of 0.087 (p> 0.05) the research data spread normally and met the normality assumption. Homogeneous testing in this research using Levene Test, which obtained a test statistic value of 1.370 with a significance value of 0.261, then the fine motor skills of children met the assumption of homogeneity. Hypothesis testing using Paired T Different Test with a T test value of 100.625 with a significance value of <0.001. The significance value is less than the 5% significance level, indicating that the initial hypothesis (H0) was rejected. It can be concluded that there was an influence of the constructive play method with clay media on the fine motor skills of children aged 5-6 years in North Maria Village, Wawo District, Bima Regency, in 2020.